Growing season - Wellington, Nicholas (Oley, PA : Bullfrog Films, 1992)
The horticulture program at San Francisco County Jail is teaching prisoners to care for plants, animals, & themselves so they can get a new sense of self-worth & respect for life. The program, created by Catherine Sneed, now goes outside the jail to community gardens
Copy in DVD Format
VHS Format
Keywords: Sneed, Catherine; Criminals -- Rehabilitation -- California -- San Francisco; Gardening -- Therapeutic use -- California -- San Francisco; Prisoners -- California -- San Francisco